2003
DOI: 10.1111/j.1744-7429.2003.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Size and Structure of Fine Root Systems in Old‐growth and Secondary Tropical Montane Forests (Costa Rica)

Abstract: The fine root systems of three tropical montane forests differing in age and history were investigated in the Cordillera Talamanca, Costa Rica. We analyzed abundance, vertical distribution, and morphology of fine roots in an early successional forest (10–15 years old, ESF), a mid‐successional forest (40 years old, MSP), and a nearby undisturbed old‐growth forest (OGF), and related the root data to soil morphological and chemical parameters. The OGF stand contained a 19 cm deep organic layer on the forest floor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
59
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 33 publications
14
59
1
5
Order By: Relevance
“…11,no. 3 Our FRB data in the top 30 cm (219.11-875.22 g.m -2 ) are within the range reported for other tropical forests from 150 to ~1100 g.m -2 (Cavelier et al 1996, Herbert & Fownes 1999, Yavitt & Wright 2001, Hertel et al 2003, Leuschner et al 2007). In fact, Jackson et al (1997) reported an average value of 330 g.m -2 for tropical forests.…”
Section: Discussionsupporting
confidence: 82%
“…11,no. 3 Our FRB data in the top 30 cm (219.11-875.22 g.m -2 ) are within the range reported for other tropical forests from 150 to ~1100 g.m -2 (Cavelier et al 1996, Herbert & Fownes 1999, Yavitt & Wright 2001, Hertel et al 2003, Leuschner et al 2007). In fact, Jackson et al (1997) reported an average value of 330 g.m -2 for tropical forests.…”
Section: Discussionsupporting
confidence: 82%
“…Root mats are generally formed on tropical forest soils with a clearly defined Oa horizon (Vogt et al, 1983); the thick organic layers (Oe and Oa horizons) that have accumulated in some late successional forests are also known to contain higher fine root biomass per area than the mineral soil both in the tropics (Hertel et al, 2003) and in the temperate zone (Berendse et al, 1989;Coomes and Grubb, 2000;Fahey and Hughes, 1994). In addition to the concentration of fine root growth into old established Oe and Oa layers, we have shown that roots also respond rapidly to relatively recent increases in fresh leaf litter.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical forest soils are generally nutrient-poor (Jordan, 1985;Richards, 1996), nutrient cycling is tight (Vitousek, 1984) and the direct cycling of nutrients from organic matter therefore plays a major role in their nutrient budget Stark and Jordan, 1978). In some, but not all, tropical forests growing on infertile soils extensive root mats form in the humus (Oa) and fermentation (Oe) horizons (Chuyong et al, 2002;Coomes and Grubb, 1996;LaClau et al, 2004;Stark and Jordan, 1978;Stark and Spratt, 1977) and even where root mats are not formed, root proliferation into the organic layer is often substantial (Hertel et al, 2003). There exists evidence that roots colonise not only older decomposing organic matter but also freshly fallen leaves (Jordan and Escalante, 1980;Herrera et al, 1978), and in a site in Southern Venezuela it has been shown that root contact with fresh litter accelerates the decomposition process and the release of Ca and Mg from the litter (Cuevas and Medina, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Oaks of this size predominately occur on the west facing slopes and in areas over 2,400 m high, and are not found in other regions of the country. In addition to a presumed high aboveground biomass, these forests also have a high fine root biomass (Hertel et al 2003). Although data are not available, one may assume that productivity is also relatively high in this high-elevation forest type.…”
Section: Introductionmentioning
confidence: 99%